2007
DOI: 10.1089/jmf.2006.030
|View full text |Cite
|
Sign up to set email alerts
|

Antihyperglycemic Property ofTragia cannabinain Streptozotocin-Induced Diabetic Rats

Abstract: The present study was performed to investigate the efficacy of an ethanol extract of the roots of Tragia cannabina for antihyperglycemic and antioxidant effects in streptozotocin (STZ)-induced diabetic rats. Male Wistar rats were administered T. cannabina (250 mg/kg) orally for 21 days, and blood glucose level was measured weekly. At the end of 21 days, concentrations of serum lipids such as total cholesterol, triglycerides, and high-density lipoprotein (HDL) and protein markers such as total protein, albumin,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
9
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 18 publications
7
9
0
Order By: Relevance
“…Elevated levels of aminotransferases in the serum are a common sign of liver and kidney damage and are observed more often among diabetics than in the general population (43). This study shows that the levels of liver aminotransferase (ALT and AST) increased significantly in STZ-induced diabetic untreated rats as shown in Tables 7 and 8, respectively.…”
Section: Enzymes Studiedsupporting
confidence: 54%
“…Elevated levels of aminotransferases in the serum are a common sign of liver and kidney damage and are observed more often among diabetics than in the general population (43). This study shows that the levels of liver aminotransferase (ALT and AST) increased significantly in STZ-induced diabetic untreated rats as shown in Tables 7 and 8, respectively.…”
Section: Enzymes Studiedsupporting
confidence: 54%
“…Ethanolic extract of T. cannabina leaf at an oral dose of 250 mg/kg, showed remarkable antihyperglycemic and antioxidant effects in STZ-induced diabetic rats. This study also confirmed the nontoxic properties of the ethanolic extract of T. cannabina leaf (Sivajothi et al, 2007). Moreover, the antidiabetic effect of an isolated phytocompound, 4-oxo-4H-pyran-2,6-dicarboxylic acid-bis-[6-methyl-heptyl] ester from T. cannabina have been demonstrated using in vitro streptozotocin (STZ) -treated chick embryo and in silico docking studies targeting active sites of AMPK (Sivajothi and Dakappa, 2014).…”
Section: Tragia Cannabinasupporting
confidence: 73%
“…The present study was designed to observe the altered morphology of kidney and kidney enzyme levels in STZ-induced diabetes at various time intervals and to investigate a possible association between diabetic nephropathy and kidney enzymes alterations. Elevated activities of serum aminotransferases are a common sign of kidney damage and are observed more frequently among people with diabetes than in general population (Fadillioglu et al;Sivajothi et al, 2007;AlShamsi et al, 2006;McAnuff-Harding et al, 2006;Ohaeri, 2001). …”
Section: Discussionmentioning
confidence: 99%